Analysis of The Accounting System For Payment of Hajj Pilgrimage Costs and Internal Control of Hajj Departures According To A Sharia Perspective at The Ministry of Religion Office - Simanullang, Ruh Kaya; Kamilah (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
The purpose of BPIH payments is to cover the remaining BPIH shortfall (cost). Hajj performance) the amount of BPIH determined by the Government is IDR 39,886,009 per person for 2022. Internal control of Hajj descent is carried out using the onboard Hajj computer system. This study was conducted to determine the BPIH payment system in accordance with Minister of Religion Regulation No. 28 2015 and the form of internal control of Pilgrimage results in accordance with Minister of Religion Decree No. 29, 2015, and to find out its implementation in accordance with the Sharia perspective. Data acquisition was carried out using the Interview Method for Hajj Officials from the Bengkalis District. The data obtained was then analyzed using qualitative methods. This study score shows that the internal billing and control system of BPIH for Hajj descendants is regulated by order of the Minister of Religion 28 and 29 2015, but is not yet optimal. Likewise, from a sharia perspective, it has not been implemented.